The Impact of Routines on Resource Management: Challenges Facing Nonprofit Organisations - Broughton, Hannah Mary (2008)
This paper explores the role of routines in the management of resources. Routines are considered a source of change or stability depending on certain factors, including how resources may be transformed by changes in routines. Charities face significant additional challenges in resource management which provide a particularly interesting environment for study. This paper examines the routines and resources of a strongly hierarchical nonprofit organisation currently undergoing significant change. The findings challenge understanding of the embeddedness factor by looking at how hierarchies can create pockets of conflicting change and consider how the relationships between the ostensive and performative aspects of routines are mediated by their implicit or explicitness in creating or restricting change.